2017
DOI: 10.1080/23328940.2017.1338210
|View full text |Cite
|
Sign up to set email alerts
|

Time-motion analysis as a novel approach for evaluating the impact of environmental heat exposure on labor loss in agriculture workers

Abstract: Introduction: In this study we (i) introduced time-motion analysis for assessing the impact of workplace heat on the work shift time spent doing labor (WTL) of grape-picking workers, (ii) examined whether seasonal environmental differences can influence their WTL, and (iii) investigated whether their WTL can be assessed by monitoring productivity or the vineyard manager's estimate of WTL. Methods: Seven grape-picking workers were assessed during the summer and/or autumn via video throughout four work shifts. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
104
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 31 publications
7
104
0
Order By: Relevance
“…Therefore, even if we consider these possible biases, we can still conclude that climate-change mitigation is indispensable for minimizing the climate-change impacts, regardless of the implementation of working time shift. Moreover, a larger portion of economic loss is caused by the construction sector (Figure 6b), and the current working time in the construction sector is not as early as that of the agricultural sector (Bates et al, 2010;Bodin et al, 2016;Chan & Yang, 2016;Chan et al, 2017;Crowe et al, 2010Crowe et al, , 2013Delgado Cortez, 2009;Hassan et al, 2017;Inaba & Mirbod, 2007;Ioannou et al, 2017;Maiti, 2008;Meade et al, 2017Meade et al, , 2015Miller et al, 2011;Sahu et al, 2013;Vatani et al, 2016, summarized in Table S4). In the sensitivity analysis, up to 3 hr of shift was assumed during the base period for the construction sector as well as the agricultural sectors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, even if we consider these possible biases, we can still conclude that climate-change mitigation is indispensable for minimizing the climate-change impacts, regardless of the implementation of working time shift. Moreover, a larger portion of economic loss is caused by the construction sector (Figure 6b), and the current working time in the construction sector is not as early as that of the agricultural sector (Bates et al, 2010;Bodin et al, 2016;Chan & Yang, 2016;Chan et al, 2017;Crowe et al, 2010Crowe et al, , 2013Delgado Cortez, 2009;Hassan et al, 2017;Inaba & Mirbod, 2007;Ioannou et al, 2017;Maiti, 2008;Meade et al, 2017Meade et al, , 2015Miller et al, 2011;Sahu et al, 2013;Vatani et al, 2016, summarized in Table S4). In the sensitivity analysis, up to 3 hr of shift was assumed during the base period for the construction sector as well as the agricultural sectors.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these studies indicate that although action plans are available for these counties, there are large knowledge gaps on effective methods to mitigate heat stress and address associated risk amongst the agricultural workers. Recently, Ioannou et al (2017) applied time-motion analysis as a novel approach for evaluating the impact of environmental heat exposure on labor loss in agriculture workers in Greece and it is quite clear that heat is a pertinent problem for European workers already at current summer temperatures. But apart from that study there appears to be a marked gap in the knowledge of workplace heat on agricultural workers in Europe and it is unclear if knowledge amongst workers and advisers is sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Ioannou et al demonstrated that 12.4% of the total work shift time was lost on irregular breaks in which the majority of the breaks were observed in the middle 4-h period of the work shift. More importantly, a higher total break time and a decreased duration of uninterrupted labor was found with an increasing WBGT and skin temperature [2]. These findings show that workplace heat stress leads to a reduced productivity of agriculture workers.…”
mentioning
confidence: 57%
“…Alternatively, timemotion analysis, in which movement and time spent on each movement is examined using video analysis, can be used to obtain insight into the physiological demands and movement patterns of an individual [1]. In the current study, Ioannou and colleagues explored the applicability of time-motion analysis to determine the impact of heat stress on labor loss in agriculture workers [2]. For this purpose, the authors assessed the impact of wet bulb globe temperature (WBGT) on work time spent in irregular work breaks of grape-picking workers [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation